The PROCESSING OF TOFU INDUSTRIAL WASTEWATER USING BIOCOAGULANT ALOE VERA GEL - Vita Kumalasari (Universitas Muhammadiyah Kalimantan Timur, 2021)
Tofu is a popular dish in Indonesia. If tofu production increases, it will also increase the produced waste. If the produced waste is not processed properly, it will cause environmental pollution which can cause health problems. One of the commonly used wastewater treatment methods is namely coagulation-flocculation. Aloe vera functions as a biocoagulant because it contains complex carbohydrates and sugars that can bind particles in the water, and contains a coagulant active substance called as mucilago. This research is an experimental research using the One Group Pretest-Posttest Design research design. Samples of tofu industrial wastewater were taken from the home industry in Janten Village, Ngestiharjo Village, Kasihan, Bantul, DIY. The addition of aloe vera gel as much as 60 ml/L in the tofu industrial wastewater caused a decrease in pH by 11.19%, COD 42.60%, BOD 44.80% and increasing TSS by 8.85%. It shows that aloe vera is effective to reduce COD and BOD in tofu industrial wastewater. Nevertheless, it is not effective to increase the pH of acidic tofu industrial wastewater and decreasing its TSS value.